Fatty acid degradation plays an essential role in proliferation of mouse female primordial germ cells via the p53-dependent cell cycle regulation. Issue 3 (1st February 2016) - Teng, Hui; Sui, Xuesong; Zhou, Cheng; Shen, Cong; Yang, Ye; Zhang, Pang; Guo, Xuejiang; Huo, Ran
ABSTRACT: Primordial germ cells (PGCs) are embryonic founders of germ cells that ultimately differentiate into oocytes and spermatogonia. Embryonic proliferation of PGCs starting from E11.5 ensures the presence of germ cells in adulthood, especially in female mammals whose total number of oocytes declines after this initial proliferation period. To better understand mechanisms underlying PGC proliferation in female mice, we constructed a proteome profile of female mouse gonads at E11.5. Subsequent KEGG pathway analysis of the 3, 662 proteins profiled showed significant enrichment of pathways involved in fatty acid degradation. Further, the number of PGCs found in in vitro cultured fetal gonads significantly decreased with application of etomoxir, an inhibitor of the key rate-limiting enzyme of fatty acid degradation carnitine acyltransferase I (CPT1). Decrease in PGCs was further determined to be the result of reduced proliferation rather than apoptosis. The inhibition of fatty acid degradation by etomoxir has the potential to activate the Ca 2+ /CamKII/5′-adenosine monophosphate-activated protein kinase (AMPK) pathway; while as an upstream activator, activated AMPK can function as activator of p53 to induce cell cycle arrest. Thus, we detected the expressional level of AMPK, phosphorylated AMPK (P-AMPK), phosphorylated p53 (P-p53) and cyclin-dependent kinase inhibitor 1 (p21) by Western blots, the results showed increased expression of them after treatment with etomoxir, suggested the activation of p53 pathway was the reason for reduced proliferation of PGCs. Finally, the involvement of p53-dependent G1 cell cycle arrest in defective proliferation of PGCs was verified by rescue experiments. Our results demonstrate that fatty acid degradation plays an important role in proliferation of female PGCs via the p53-dependent cell cycle regulation.